L-carnitine as an ergogenic aid for patients with chronic obstructive pulmonary disease submitted to whole-body and respiratory muscle training programs - Borghi-Silva, A.; Baldissera, V.; Sampaio, L. M. M.; Pires-DiLorenzo, V. A.; Jamami, M.; Demonte, Aureluce [UNESP]; Marchini, J. S.; Costa, D. (Associação Brasileira de Divulgação Científica (ABRADIC), 2006)
The effects of adding L-carnitine to a whole-body and respiratory training program were determined in moderate-to-severe chronic obstructive pulmonary disease (COPD) patients. Sixteen COPD patients (66 ± 7 years) were randomly assigned to L-carnitine (CG) or placebo group (PG) that received either L-carnitine or saline solution (2 g/day, orally) for 6 weeks (forced expiratory volume on first second was 38 ± 16 and 36 ± 12%, respectively). Both groups participated in three weekly 30-min treadmill and threshold inspiratory muscle training sessions, with 3 sets of 10 loaded inspirations (40%) at maximal inspiratory pressure. Nutritional status, exercise tolerance on a treadmill and six-minute walking test, blood lactate, heart rate, blood pressure, and respiratory muscle strength were determined as baseline and on day 42. Maximal capacity in the incremental exercise test was significantly improved in both groups (P < 0.05). Blood lactate, blood pressure, oxygen saturation, and heart rate at identical exercise levels were lower in CG after training (P < 0.05). Inspiratory muscle strength and walking test tolerance were significantly improved in both groups, but the gains of CG were significantly higher than those of PG (40 ± 14 vs 14 ± 5 cmH2O, and 87 ± 30 vs 34 ± 29 m, respectively; P < 0.05). Blood lactate concentration was significantly lower in CG than in PG (1.6 ± 0.7 vs 2.3 ± 0.7 mM, P < 0.05). The present data suggest that carnitine can improve exercise tolerance and inspiratory muscle strength in COPD patients, as well as reduce lactate production.
Keywords: Chronic obstructive pulmonary disease; L-carnitine; Exercise training; Respiratory muscle training; Blood lactate